The urgency of implementing halal product process assistance: Review of maqashid syariah - Muhamad Hilmi Al Ghifari; Prima Dwi Priyatno (UIN Siber Syekh Nurjati Cirebon, 2024)
Halal food commodities are currently a priority aspect for the Indonesian government, to the point of creating a self-declare scheme intended for micro and small business actors. Since the implementation of the self-declare scheme, it has positively impacted the achievement of the halal certificate target. However, problems also create doubts about the mechanisms implemented in society. Therefore, this article aims to increase assistants' understanding by correlating work procedures with maqashid shariah values. To produce an informative discussion, a qualitative descriptive method with a literature study approach is used in this article. After going through all the research stages, the results were obtained, and the procedures for checking ingredients, processing halal products, and correcting findings were classified as maslahah dharuriyyah. Thus, it can be concluded that all of these stages contain safeguards or protection against the objectives of the sharia (maqashid sharia), especially the hifdz din, hifdz nafs, and hifdz aql points.. Therefore, halal product process assistants must understand and implement the maqashid shariah values to produce performance output that benefits society.Keywords: Maqashid Shariah; Halal Product Process; Self-Declare